Crazy Culture the Sins of Civilization. - Heinegg, Peter (Lanham : University Press of America, 2012)
.Cs676C7CC9{text-align:left;text-indent:0pt;padding:12pt 0pt 0pt 0pt;margin:0pt 0pt 12pt 0pt}.csA62DFD6A{color:#000000;background-color:transparent;font-family:Times New Roman; font-size:12pt; font-weight:normal; font-style:italic; }.cs5EFED22F{color:#000000;background-color:transparent;font-family:Times New Roman; font-size:12pt; font-weight:normal; font-style:normal; }Crazy Culture is a series of broadsides against many widely held misconceptions in both academe and the general public. Surveying the history and ideology of cultural realms such as religion, sexual norms, politics, economics.
Prelude; Introduction; Chapter One. The Primal Sin; Chapter Two. The Sexist Sins; Chapter Three. The Religious Sins; Chapter Four. The Urban Sins; Chapter Five. The Sins of Technology; Chapter Six. The Economic Sins; Chapter Seven. The Political Sins; Chapter Eight. The Narcissistic Sins; Chapter Nine. The Artistic Sins; Chapter Ten. The Ludic Sins; Conclusion.
Print version record.
Keywords: Culture; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Culture; Electronic books; Electronic books